Bioethanol production from sugarcane bagasse using escherichia coli K011 - Amira Dayana, Abd. Rahman (Universiti Malaysia Sarawak (UNIMAS), 2015)
Sugarcane bagasse is one of the most abundant lignocellulosic biomass that can be found in Malaysia and this biomass can be used to produce bioethanol. In this study, bioethanol had been produced by using the Simultaneous co-Saccharification and Fermentation (Sc-SF) process. The addition of cellulase enzyme for the saccharification process had been added at the earliest stage of the fennentation process. Cellulase enzyme helped in the hydrolysis of cellulose to simpler substances such as glucose that later being used for the fermentation process. Escherichia coli KO II were used in this study as the ethanolic fennenters. Samples from each ofthe fennentation vessels had been analysed by using High Perfonnance Liquid Chromatography (HPLC). The samples were also being analysed for reducing sugars and total carbohydrate concentrations by using Phenol-Sulphuric Acid test and 3,5-dinitrosalicyclic acid (DNS) colorimetric method. The highest amount of bioethanol and acetic acid produced in Simultaneous co-Saccharification and Fennentation (ScSF) had been recorded by 2.50% fresh feedstock loading with the amount of 3.87 giL and 3.71 giL respectively. The best feedstock loading for the production of bioethanol is 2.50% fresh feedstock loading. This study indicated that it is possible to produce bioetha_nol without any pre-treatment on sugarcane bagasse.